New understanding of inter-ELM pedestal turbulence, transport, and gradient behavior in the DIII-D tokamak. (9th November 2021) - Barada, K.; Rhodes, T.L.; Haskey, S.R.; Groebner, R.; Diallo, A.; Banerjee, S.; Zeng, L.; Yan, Z.; Chen, J.; Laggner, F.; Wang, G.
Abstract: New observations of pedestal localized turbulence in the inter-ELM period of H-mode plasmas in DIII-D show that ion temperature gradient mode scale (ITG-scale) density fluctuation ( ñ ) increases immediately after each ELM crash and is quickly suppressed during the increase in local E × B shear. This excitation and subsequent suppression of ITG-scale ñ can explain the previously reported anomalous ion heat flux, Q i during the ELM (Viezzer et al 2017 Nucl. Fusion 57 022020). Shorter wavelength trapped electron mode scale (TEM-scale) ñ starts to increase at a critical pedestal temperature gradient (∇ T e, ped ) and saturates as local E × B shear, T i C 6 + / T e ratio, and ∇ T e, ped saturate. This TEM-scale ñ, which has the potential to cause electron (and also ion) heat transport, is consistent with driving an anomalous electron heat flux Q e, where Q e is estimated between ELMs using experimental profiles and power balance. Both ITG- and TEM-scale ñ amplitude variations with background T i / T e and ∇ n e, ped are found to be consistent with theoretical predictions of these measured density fluctuations being ITG and TEM instabilities respectively. These new and unique observations on the nature of turbulence and their potential contributions to electron and ion heat fluxes at different ELM periods (i.e. collapse, recovery, and saturation phases of pedestal gradients) can significantly test and improve our pedestal predictive capabilities for ITER and other future fusion devices.